Improvement of the lending mechanism for agricultural production in the countries of the Eurasian Economic Union - Narynbayeva, A.S.; Smagulova, Z.K.; Soltangazinov, A.R. (BUKETOV BUSINESS REVIEW, 2018)
The article examines the topicality, problems, theoretical and methodological approaches to improve the credit system in the production of competitive agricultural products and food in the EAEUcountries. The purpose of the study is to analyze the mechanism of lending and its impact on the development of agricultural production, as one of the priority areas in the context of integration of national economies. The agrarian policy of the EAEU states in the sphere of crediting is not yet sufficiently unified and differs in variety. In order to determine the role and place of agriculture in the economy of the EAEU member countries, a comparative analysis of the volume of state financial support is presented, the indicators of the gross added value of agriculture in GDP, labor productivity, and the share of credits in the economy of the country are analyzed. The article considers the mechanism of state management of agricultural production to provide financial resources in Kazakhstan, Russia, Belarus: lending, leasing services. Eurasian integration will reduce the costs of transportation, storage, sale of agricultural products and food, create new market institutions. The introduction of a unified mechanism of state management in the EAEUcountries, in theauthors opinion, will make it possible to equip agricultural producers in equal economic conditions, increase production efficiency and competitiveness in the world markets for agricultural raw materials and foodstuffs, as well as solve the problem of providing the population with food and other issues of economic development in the EAEU countries.